Improving the Infant's or Toddler's Safety Helmet using Industrial Engineering Design Techniques - Sivanantha, Chandrasekara Pandian (2015)
For many beings, learning to walk in a world of hard surfaces can turn a special moment into a heart rendering incident in a flash. But now toddlers have better protection with a step further to secure their head. Subsequently, the aim of this study was to assess the infant’s or toddler’s safety helmet and to aid redesigning the improvements on the safety helmet based on several designing techniques of industrial engineering. Further designing of the improvements made on the safety helmet was carried out using the AutoCAD and solid works where else a 3D printer was used to print out the chin guard and mouth guard. A list of vital designing methods needs to be accomplished in order to get a better perspective on what the customer really needs concerning the safety helmet for the infants or toddlers. Beginning with survey then observing the users later signifying objective tree method and last of all house of quality. Once these methods were completed, the designing processes of the improvements made on the toddler’s safety helmet were started based on the requirements and results obtained from the design methods carried out. Over and done with that, the chin guard, mouth guard, a knob at the end of the chin strap and straps on top of the helmet were upgraded on the safety helmet. Above these expansions, the infant’s or toddler’s safety helmet can further protect the user effectively and efficiently with no further injuries.